Synthesis and anticholinesterase activity of new substituted benzo[d]oxazole‐based derivatives. (11th December 2016) - Pouramiri, Behjat; Moghimi, Setareh; Mahdavi, Mohammad; Nadri, Hamid; Moradi, Alireza; Tavakolinejad‐Kermani, Esmat; Firoozpour, Loghman; Asadipour, Ali; Foroumadi, Alireza
Abstract : A series of novel benzo[ d ]oxazole derivatives (6a–n ) have been synthesized and biologically evaluated as potential inhibitors of acetylcholinesterases (AChE) and butyrylcholinesterase (BChE). The chemical structures of all final compounds were confirmed by spectroscopic methods. In vitro studies showed that most of the synthesized compounds are potent acetylcholinesterase and butyrylcholinesterase inhibitors. Among them, compounds6a and6j strongly inhibited AChE and BChE activities with IC50 values of 1.03–1.35 and 6.6–8.1 μm, respectively. Docking studies also provided the binding modes of action and identified hydrophobic pi forces as the main interaction. Abstract : A series of novel benzo[ d ]oxazole‐based derivatives were synthesized as novel anticholinesterase agents. The inhibitory activities against AChE and BChE were more potent than donepezil. 2‐(4‐((Piperidin‐1‐yl)methyl)phenyl)benzo[ d ]oxazole exhibited dual inhibitory activity against BChE (two times stronger than reference drug) and moderate activity against AChE.